Persepsi Mahasiswa Vokasi Aks-Akk Terhadap Penggunaan Aplikasi Quizizz pada Mata Kuliah Pengetahuan Tata Busana - Wahyu Eka Priana Sukmawaty; Yosephine Flori Setiarini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine students' perceptions of using the quizizz application in the Fashion Knowledge course. The research method used is a convergent parallel mixture. The sampling technique uses purposive sampling, which is based on the primary consideration of who can provide the best information to achieve the objectives of this study, and the number of samples can be determined based on the study's objectives. The sample used was 32 students of the fashion design study program in semester 1 of FY 2021/2022. Data collection techniques in this study used interviews and documentation. For quantitative data collection using go. The form was distributed to 32 students. Meanwhile, to collect qualitative data through in-depth interviews with five students. Data analysis techniques use the Miles and Huberman model, which consists of data collection, data reduction, data display, and conclusion. The result of this study is that in using the quizizz application in this Fashion Knowledge course, there is an element of an update following the development of industry 4.1. The use of quizizz also provides satisfaction to students because of the transparency in finding out the final score obtained from the evaluation. The ease of using quizizz is felt by students because they can do fashion knowledge course questions anywhere, even if they only use cell phones. Students are more motivated in fashion knowledge lessons after using the quizizz application, especially practicing practice questions to continue practicing and reading to get a high score.